Development of Student Attendance Information System at SMK Negeri 9 Medan - Zen, Muhammad; Wijaya, Rian Farta; Irwan, Irwan (International Conference on Sciences Development and Technology, 2022)
The conventional attendance process takes a long time during attendance and also during recording. Absenteeism recapitulation helps teachers monitor student attendance in class. In addition, attendance recapitulation can be one of the considerations in the assessment. The information system can help the conventional attendance recapitulation process become automatic. Vocational High School (SMK) Negeri 9 is a school located in Medan City, North Sumatra. SMK Negeri 9 Medan has 5 majors with a total of 2077 students. Attendance management still uses conventional methods so it is necessary to conduct research related to the development of student attendance information systems. The methodology used in this research is problem identification, system requirement identification, data collection, system analysis and development. This study aims to facilitate the attendance process and attendance recapitulation. System development uses the Use Case Diagram model and Entity Relationship Diagram. The Use Case Diagram helps answer the functional requirements of the system desired by the school. While the Entity Relationship Diagram describes the database model. The model can be corrected to get the best results in database development.